2023
DOI: 10.3389/fonc.2023.1178123
|View full text |Cite
|
Sign up to set email alerts
|

A new model based on gamma-glutamyl transpeptidase to lymphocyte ratio and systemic immune-inflammation index can effectively predict the recurrence of hepatocellular carcinoma after liver transplantation

Abstract: BackgroundLiver transplantation (LT) is one of the most effective treatment modalities for hepatocellular carcinoma (HCC), but patients with HCC recurrence after LT always have poor prognosis. This study aimed to evaluate the predictive value of the gamma-glutamyl transpeptidase-to-lymphocyte ratio (GLR) and systemic immune-inflammation index (SII) in terms of HCC recurrence after LT, based on which we developed a more effective predictive model.MethodsThe clinical data of 325 HCC patients who had undergone LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…39 GLR could be used as a potential prognostic marker of early recurrence and prognosis, and higher GLR is associated with poor outcomes. [40][41][42] INR is 1122 a good measure of hepatic synthetic function. A large cohort study including 2509 HCC patients showed that low INR levels had shorter RFS and OS compared to high INR levels.…”
Section: Discussionmentioning
confidence: 99%
“…39 GLR could be used as a potential prognostic marker of early recurrence and prognosis, and higher GLR is associated with poor outcomes. [40][41][42] INR is 1122 a good measure of hepatic synthetic function. A large cohort study including 2509 HCC patients showed that low INR levels had shorter RFS and OS compared to high INR levels.…”
Section: Discussionmentioning
confidence: 99%